Reduction of Matrix Metallopeptidase 13 and Promotion of Chondrogenesis by Zeel T in Primary Human Osteoarthritic Chondrocytes - Sanchez, Christelle; Hemmer, Kathrin; Krömmelbein, Natascha; Seilheimer, Bernd; Dubuc, Jean-Emile; Antoine, Christophe; Henrotin, Yves (Frontiers in Pharmacology, 2021)
Objectives: Zeel T (Ze14) is a multicomponent medicinal product. Initial preclinical data suggested a preventive effect on cartilage degradation. This study aimed to explore these effects further to better understand the mode of action of Ze14 on human OA chondrocytes in vitro. Methods: Primary chondrocytes were obtained from the knees of 19 OA patients and cultured either as monolayers or in alginate beads. The cultures were treated with 20 % or 10 % (v/v) Ze14 or placebo. For RNA-seq, reads were generated with Illumina NextSeq5000 sequencer and aligned to the human reference genome (UCSC hg19). Differential expression analysis between Ze14 and placebo was performed in R using the DESeq2 package. Protein quantification by ELISA was performed on selected genes from the culture medium and/or the cellular fractions of primary human OA chondrocyte cultures. Results: In monolayer cultures, Ze14 20 % (v/v) significantly modified the expression of 13 genes in OA chondrocytes by at least 10 % with an adjusted p-value < 0.05 : EGR1, FOS, NR4A1, DUSP1, ZFP36, ZFP36L1, NFKBIZ and CCN1 were upregulated and ATF7IP, TXNIP, DEPP1, CLEC3A and MMP13 were downregulated after 24 h Ze14 treatment. Ze14 significantly increased (mean 2.3-fold after 24 h, p=0.0444 and 72 h, p=0.0239) the CCN1 protein production in human OA chondrocytes. After 72 h, Ze14 significantly increased type II collagen pro-peptide production by mean 27 % (p=0.0147). For both time points CCN1 production by OA chondrocytes was correlated with aggrecan (r=0.66, p=0.0004) and type II collagen pro-peptide (r=0.64, p=0.0008) production. In alginate beads cultures, pro-MMP-13 was decreased by Ze14 from day 7 to day 14 (from -16 to -25 %, p<0.05) and from day 17 to 21 (-22 %, p=0.0331) in comparison to controls. Conclusion: Ze14 significantly modified the expression of DUSP1, DEPP1, ZFP36/L1 and CLEC3A, which may reduce MMP13 expression and activation. Protein analysis confirmed that Ze14 significantly reduced the production of pro-MMP-13. As MMP-13 is involved in type II collagen degradation, Ze14 may limit cartilage degradation. Ze14 also promoted extracellular matrix formation arguably through CCN1 production, a growth factor well correlated with type II collagen and aggrecan production.